THE PHILOSOPHY OF CHIVALRY AND BRAVERY IN POWER SPORTS (Journal of Teleological Science, 2023)
The purpose of this article is to examine the philosophy of chivalry and bravery in the sport of powerlifting. The philosophy and worldview of Iranians has been a philosophy of struggle since ancient times, and since long ago the call to help Ahura Mazda in the fight against the devil has been recognized as a sacred invitation. The discussion here is about how this philosophy and worldview, after Islam, is compatible with the rituals of the school of Fatut. Or the ritual of chivalry has continued as a social policy of Iranians. Conducting research is descriptive-analytical and documentary. The results of the research show that the religion of chivalry has spread and rooted with the use of principles such as spirituality and moral principles based on Islamic values, justice and kindness, with the efforts of chivalry and wrestlers in the sport of strength, which shows high human emotions and historical populism. It is Iranians. In Islam, fatut is considered as one of the characteristics of religion and a perfecting quality for mystics, and it is a contract between a disciple and a profession, it is a moral that leads to the refinement of morals and the strengthening of brotherhood among people, and calls to virtues and courage, and avoiding vices and cowardice. Islamic fatwat in Zorkhane sports, and the customs and ceremonies of the people of Zorkhane have their roots in Iranian-Islamic history and identity, and its spread in other sports has a wide reflection in criticizing the anomalies that rule the society, and increasing the true and authentic social and economic values. The fight against oppression and corruption will be done and these mystical professions can be introduced as a suitable moral model for the sports of today's youth.
Keywords: philosophy of chivalry; Islamic fatwat; forced sports